2018
DOI: 10.1002/ppsc.201700447
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐Containing Self‐Nanoemulsifying Drug Delivery System for Enhance Stability and Oral Absorption of trans‐Resveratrol

Abstract: Self‐nanoemulsifying drug delivery system (SNEDDS) is recently studied for enhancing the bioavailability of hydrophobic drugs, such as resveratrol (RSV). However, the functional design of SNEDDS for the drug structural protection is not studied yet. Here, this paper presents an efficient approach by adding lignin (a kind of abundant biomass resource) to enhance the stability of trans‐RSV and meantime improve its oral bioavailability. Higher stability of trans‐RSV (just decreased 2% to cis‐RSV after 1 h under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Various pharmacokinetic parameters revealed directly the enhanced adsorption rate of RSV SNEDDS. The AUC of the proposed formulation resulted in a 72‐fold increase in bioavailability and C max value rose considerably to 24 fold as compared to RSV suspended in water . Similarly, in vivo studies revealed a 5‐fold increase of the bioavailability of RSV encapsulated in solid lipidic nanoparticles compared to RSV suspension.…”
Section: Overcoming Limitationsmentioning
confidence: 86%
See 4 more Smart Citations
“…Various pharmacokinetic parameters revealed directly the enhanced adsorption rate of RSV SNEDDS. The AUC of the proposed formulation resulted in a 72‐fold increase in bioavailability and C max value rose considerably to 24 fold as compared to RSV suspended in water . Similarly, in vivo studies revealed a 5‐fold increase of the bioavailability of RSV encapsulated in solid lipidic nanoparticles compared to RSV suspension.…”
Section: Overcoming Limitationsmentioning
confidence: 86%
“…For example, the isomer degradation in the SNEDDS was evaluated inside and outside the dialysis bag. Interestingly, the results showed that SNEDDS greatly reduced the photochemical degradation of trans ‐RSV, whereas the amount released and degraded of RSV from free solution was 50–50 (Figure ), which may be due to the directly contact with light and oxygen …”
Section: Overcoming Limitationsmentioning
confidence: 99%
See 3 more Smart Citations